Annual plant reviews, Volume 17: Plant architecture and its manipulation - Turnbull, Colin (Blackwell, 2012)
"This book provides a broad coverage of our current understanding of plant architecture and its manipulation, ranging from the architecture of the individual cell to that of the whole plant. It is directed at researchers and professionals in plant physiology, developmental biology, molecular biology, genetics and biotechnology."